The applications of biotechnology to disease resistance breeding in oat - Scoles, Graham; Eckstein, Peter (MTT, 2004)
Through the use of biotechnology, molecular marker assisted selection and genetic engineering can both contribute to disease resistance breeding. A number of markers for various oat diseases have been identified and some are being used in breeding programs. Genetic engineering of oat is now well established but genetic engineering for disease resistance in any crop is still in its infancy and remains to be proven in the field.
Keywords: Ka; Biotechnology; disease resistance; markers; genetic engineering